2018
DOI: 10.1016/j.tibtech.2018.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell Microgels: Technology, Challenges, and Applications

Abstract: Single-cell-laden microgels effectively act as the engineered counterpart of the smallest living building block of life: a cell within its pericellular matrix. Recent breakthroughs have enabled the encapsulation of single cells in sub-100-μm microgels to provide physiologically relevant microniches with minimal mass transport limitations and favorable pharmacokinetic properties. Single-cell-laden microgels offer additional unprecedented advantages, including facile manipulation, culture, and analysis of indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
60
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(65 citation statements)
references
References 108 publications
1
60
0
Order By: Relevance
“…To enhance residence time, Mao et al recently demonstrated a microencapsulation technique, in which individual MSCs were encapsulated in alginate-poly- d -lysine (PDL)-alginate (APA) microgels (particulate hydrogels with dimensions in the range of 30 to 50 μm). Using a single-cell microgel encapsulation approach has several distinct advantages compared to typical larger multicellular hydrogels for systemic administrations: The advantages include a reduced fibrotic capsule formation, a reduction in diffusion limitations that lead to hypoxic effects, and a higher surface area to volume ratio, which facilitates the release of biologics from encapsulated cells ( 125 ). Specifically, in the study by Mao et al , unlike a regular hydrogel that has a large volume and is not suitable for intravenous injection, the encapsulating microgel layer is on the order of 10 μm and can be easily injected intravenously.…”
Section: Overcoming Clinical Challenges From Administrationmentioning
confidence: 99%
“…To enhance residence time, Mao et al recently demonstrated a microencapsulation technique, in which individual MSCs were encapsulated in alginate-poly- d -lysine (PDL)-alginate (APA) microgels (particulate hydrogels with dimensions in the range of 30 to 50 μm). Using a single-cell microgel encapsulation approach has several distinct advantages compared to typical larger multicellular hydrogels for systemic administrations: The advantages include a reduced fibrotic capsule formation, a reduction in diffusion limitations that lead to hypoxic effects, and a higher surface area to volume ratio, which facilitates the release of biologics from encapsulated cells ( 125 ). Specifically, in the study by Mao et al , unlike a regular hydrogel that has a large volume and is not suitable for intravenous injection, the encapsulating microgel layer is on the order of 10 μm and can be easily injected intravenously.…”
Section: Overcoming Clinical Challenges From Administrationmentioning
confidence: 99%
“…The bottom‐up assembly of microtissues allows in situ printing or implantation of replacement organs or therapeutic agents such as stem cells to be delivered in a noninvasive or mini‐invasive manner. Hydrogel microparticles encapsulating therapeutic stem cells has been found to significantly increase the retention rate of such cells at the transplant site . Scarless wound healing has been a challenge associated with many surgical procedures, but may be avoided by in situ assembly of modular microtissues via mini‐invasive transplantation.…”
Section: Challenges and The Future Directionsmentioning
confidence: 99%
“…Scarless wound healing has been a challenge associated with many surgical procedures, but may be avoided by in situ assembly of modular microtissues via mini‐invasive transplantation. Moreover, it was found that the cell‐laden microgels (soft microtissues) smaller than 100 µm in diameter had dramatically reduced effect as implants to induce fibrosis, compared with larger implants . Finally, microgels are capable of providing immunoprotection and meanwhile allowing efficient insulin release from encapsulated islet cells …”
Section: Challenges and The Future Directionsmentioning
confidence: 99%
“…This deepened understanding of tissue‐specific microenvironments and recognition of their fundamental modular nature has revealed that different cell populations and their supportive extracellular matrix (ECM) represent the core effectors in human biological systems and are essential for life . During the processes of organogenesis and morphogenesis, such elements self‐orchestrate tissue development from a nano‐ to macrostructural organization in a dynamic mode involving both cell–cell crosstalk (e.g., via soluble mediators, vesicles, etc.)…”
Section: Introductionmentioning
confidence: 99%